The impact of community-based health insurance on universal health coverage in Ethiopia: a systematic review and meta-analysis - Ewunetie Mekashaw Bayked; Husien Nurahmed Toleha; Seble Zewdu Kebede; Birhanu Demeke Workneh; Mesfin Haile Kahissay (Taylor & Francis Group, 2023)
Background Ideally health insurance aims to provide financial security, promote social inclusion, and ensure equitable access to quality healthcare services for all households. Community-based health insurance has been operating in Ethiopia since 2011. However, its nationwide impact on universal health coverage has not yet been evaluated despite several studies being conducted. Objective We evaluated the impact of Ethiopia's community-based health insurance (2012-2021) on universal health coverage. Methods On 27 August 2022, searches were conducted in Scopus, Hinari, PubMed, Google Scholar, and Semantic Scholar. Twenty-three studies were included. We used the Joana Briggs Institute checklists to assess the risk of bias. We included cross-sectional and mixed studies with low and medium risk. The data were processed in Microsoft Excel and analyzed using RevMan-5. The impact was measured first on insured households and then on insured versus uninsured households. We used a random model to measure the effect estimates (odds ratios) with a p value < 0.05 and a 95% CI. Results The universal health coverage provided by the scheme was 45.6% (OR = 1.92, 95% CI: 1.44-2.58). Being a member of the scheme increased universal health coverage by 24.8%. The healthcare service utilization of the beneficiaries was 64.5% (OR = 1.95, 95% CI: 1.29-2.93). The scheme reduced catastrophic health expenditure by 79.4% (OR = 4.99, 95% CI: 1.27-19.67). It yielded a 92% (OR = 11.58, 95% CI: 8.12-16.51) perception of health service quality. The health-related quality of life provided by it was 63% (OR = 1.71, 95% CI: 1.50-1.94). Its population coverage was 40.1% (OR = 0.64, 95% CI: 0.41-1.02). Conclusion Although the scheme had positive impacts on health service issues by reducing catastrophic costs, the low universal health coverage on a limited population indicates that Ethiopia should move to a broader national scheme that covers the entire population.